Two forms of organizational unlearning: Insights from engaged scholarship research with change consultants. Issue 5 (November 2020) - Grisold, Thomas; Klammer, Adrian; Kragulj, Florian
Following recent calls to extend our understanding of organizational unlearning, we gain empirical insights into how the process unfolds in practice. Based on the findings of a study with change consultants in Europe, we conceptualize two forms of organizational unlearning. First, open-ended unlearning refers to instances where organizational knowledge is intentionally discarded, but the outcomes of the change process are not known. Second, goal-directed unlearning refers to situations where organizations implement specified knowledge structures that are incompatible with established ones. We also find that both forms of organizational unlearning necessitate preparatory work and interventions that increase their likelihood to succeed. Outlining the implications of the organizational unlearning concept in organizational practice contributes to a better understanding of existing research. We further discuss implications for theory and outline avenues for future research.